Colorimetric Thermography by a Long‐Infrared Dual‐Band Metalens - Zhendong Luo; Peng Zhang; Huwang Hou; Yiming Li; Binzhao Li; Yanji Yi; Lianjie Xu; Ting Meng; Zihan Geng; Mu Ku Chen; Yang Zhao (Advanced Science)
Abstract Infrared (IR) radiation thermography is extensively utilized in diverse fields due to its non‐contact capability. Nevertheless, its effectiveness is often compromised by the significant emissivity variations among different objects, limiting its application to specific setups or focused object types. Colorimetric thermography is introduced as an alternative emissivity‐independent method of radiation thermometry. This technique involves measuring radiance across two or more spectral bands and calculating the object's temperature based on the signal ratio, thereby mitigating emissivity effects under certain conditions. However, this method has the trade‐off of necessitating bulky optical systems, complex filter imaging configurations, and sensor structures. To meet the requirements of IR thermography for compact structure, lightweight design, and customizability, a dual‐band metalens is developed for the IR colorimetric thermography. The central wavelengths targeted are 9.5 and 12.5 µm. The dual‐band IR imaging by the fabricated dual‐band metalens is demonstrated, and the colorimetric thermography of low‐emissivity objects is performed without presetting emissivity values. This approach significantly eliminates measurement errors associated with emissivity by an average of 50.16% across a temperature range of 60–180 °C. This innovation paves the way for dynamic and multi‐target thermography using compact IR systems in complex environments.